Inequality of Educational Opportunities and Digital Literacy of School-Age Children In Sumatra - Yollanda Alvis; Rossanto Dwi Handoyo (MediaTrend, 2021)
Inequality of educational opportunities is at the root of economic problems. Educational attainment will be a basic element in generating income, which will improve the quality and well-being of every child in the future. This study aims to look at the inequality of educational opportunities and the impact of digital literacy of school-age children on the inequality of educational opportunities in Sumatra. The results of the calculation show that there is an inequality of educational opportunities in Sumatra. Riau islands and Lampung provinces have the most ideal conditions where the inequality of education opportunities of low school age children and digital literacy of children is high. While the provinces of North Sumatra and South Sumatra have the least ideal conditions, the inequality of educational opportunities of high school-age children and digital literacy of children is low.